Analysis of Logical Thinking Ability in Natural Science Learning Using Blended Learning Based on Google Classroom - Henni Riyanti; Putri Dewi Nurhasana (Universitas Pendidikan Indonesia Kampus Serang, 2021)
The ability to use technology during the COVID-19 pandemic is needed to empower logical thinking ability as one of the 21st-century competencies. This study aims to analyze the effect of learning natural science assisted by google classroom on improving students' logical thinking abilities during COVID-19. The use of Google Classroom potentially facilitates educators to create creative, innovative, and collaborative blended learning to still build classroom interactions in social distancing period. This quasi-experimental research employed a pre-experimental one-group pretest-posttest design. The research subjects were 39 sixth-grade students. The validity and reliability of the data on the ability to think logically used a logical thinking ability instrument tested. The data analysis utilized the N-gain test with the help of SPSS 21. The results revealed that the N-gain was 82.43 or 82.4%, with a minimum N-gain score of 53.3% and a maximum of 83.5%, included in the high category (g) ≥ 0.7. Thus, it could be concluded that natural science learning assisted by Google Classroom media significantly affected students' logical thinking abilities. Educators can use the analysis results to evaluate natural science learning, especially in elementary schools, to encourage the quality of students' logical thinking abilities.